2019
DOI: 10.1007/s00223-019-00577-2
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, Autoimmune Disease and Rheumatoid Arthritis

Abstract: Vitamin D has been reported to influence physiological systems that extend far beyond its established functions in calcium and bone homeostasis. Prominent amongst these are the potent immunomodulatory effects of the active form of vitamin D, 1,25-dihydroxyvitamin D3 (1,25-(OH) 2 D3). The nuclear vitamin D receptor (VDR) for 1,25-(OH) 2 D3 is expressed by many cells within the immune system and resulting effects include modulation of T cell phenotype to suppress pro-inflammatory Th1 and Th17 CD4+ T cells and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
95
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 156 publications
0
95
1
10
Order By: Relevance
“…At the cellular level, vitamin D exerts anti-inflammatory effects on immune cells that express the vitamin D receptor (VDR) such as monocytes, macrophages, and T lymphocytes, which in turn shapes the immune response during the onset of inflammation and infection and following vaccination. Vitamin D exerts anti-inflammatory effects by reducing pro-inflammatory cytokines production from macrophages and T cells ( 12 , 13 ). Carlberg eloquently demonstrated that vitamin D/VDR signaling impacts chromatin modeling leading to significant modification of human monocytes epigenome during perturbation, consequently reducing cytokine release and modulating trained innate immunity.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…At the cellular level, vitamin D exerts anti-inflammatory effects on immune cells that express the vitamin D receptor (VDR) such as monocytes, macrophages, and T lymphocytes, which in turn shapes the immune response during the onset of inflammation and infection and following vaccination. Vitamin D exerts anti-inflammatory effects by reducing pro-inflammatory cytokines production from macrophages and T cells ( 12 , 13 ). Carlberg eloquently demonstrated that vitamin D/VDR signaling impacts chromatin modeling leading to significant modification of human monocytes epigenome during perturbation, consequently reducing cytokine release and modulating trained innate immunity.…”
mentioning
confidence: 99%
“…To confirm the inhibitory effect of VDR on NLP3 inflammasome activation, authors used VDR-deficient mice and showed that IL-1β release was significantly reduced in vivo confirming that VDR inhibited NALP3 inflammasome activation. Vitamin D deficiency is associated with bone pain in particular and chronic disease pain in general ( 12 , 14 ). The proposed mechanisms by which Vitamin D/VDR signaling modulate pain sensation is reviewed by Habib et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The potential immunomodulatory effects of vitamin D in vitro are well recognised and Harrison et al describe their potential impact in vivo, particularly in rheumatoid arthritis [12]. They present a delightfully clear figure reminding the reader of the immune mechanisms under consideration.…”
mentioning
confidence: 99%